Improving the New Zealand sign language skills of educators. (2nd October 2019) - Powell, Denise; Boon, Anita; Luckner, John
ABSTRACT: One of the most important achievements individuals accomplish is the development of a first language. However, many students who are deaf who use sign language to communicate struggle to become fluent in sign. One factor that hinders their language development is the fact that most of the adults they interact with do not sign well. The purpose of this manuscript is to share the results of a project to improve the sign skills of educators who serve students who are deaf in New Zealand. Recommendations for professional development and research are provided.